Synthesis and anti-tumor activities of new [1,2,4]triazolo[1,5-a]pyrimidine derivatives - Ahmed, Sayed Abdelkader; Ahmed, Osama Mohamed; Abdelhamid, Abdou Osman (European Journal of Chemistry, 2014)
Condensation of 1H-1,2,4-triazol-5-amine with the appropriate sodium (E)-(2-oxocycloalkylidene)methanolate gave 7,8-dihydro-6H-cyclopenta[e][1,2,4]triazolo [1,5-a]pyrimidine, 6,7,8,9-tetrahydro-[1,2,4]triazolo[1,5-a]quinazoline, 7,8,9,10-tetra hydro-6H-cyclohepta[e][1,2,4]triazolo[1,5-a]pyrimidine and 6,7,8,9,10,11-hexahydro cycloocta[e][1,2,4]triazolo[1,5-a]pyrimidine. Structures of the newly synthesized compounds were elucidated via elemental analyses, spectral (IR, 1H NMR, 13C NMR, 2D NMR), and X-ray single crystal diffraction data. These derivatives showed potent anti-tumor cytotoxic activity in vitro using different human cancer cell lines.